1995
DOI: 10.1029/94wr02853
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Moments for Classical‐, Quasi‐, and Convolution‐Fickian Dispersion of a Conservative Tracer

Abstract: Transport moments up to fourth order for convolution-, quasi-, and classical-Fickian dispersion of a conservative tracer are presented and compared. Convolution-Fickian yields a non-Gaussian distribution while quasi-and classical-Fickian result in Gaussian type distributions regardless of the distribution of a stationary velocity field. The first and second central spatial moments are the same for convolution-and quasi-Fickian dispersion, while the third and fourth central moments differ. Introduction For stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…Non-local effects can be incorporated in calculations of ~(x,t) by recognizing the simplicity of (5), for a stationary flow field, in Fourier-Laplace space (as done by Dent et al [1993] and Deng and Cushman, [1995]), or by numerically solving (4) (as first done by Graham and McLaughlin [1989]). Cushman and ttu [1995] provide a discussion on nonlocal representations of the dispersive flux.…”
Section: ~(Xt) -;(X)~(x) Oxj (4)mentioning
confidence: 99%
“…Non-local effects can be incorporated in calculations of ~(x,t) by recognizing the simplicity of (5), for a stationary flow field, in Fourier-Laplace space (as done by Dent et al [1993] and Deng and Cushman, [1995]), or by numerically solving (4) (as first done by Graham and McLaughlin [1989]). Cushman and ttu [1995] provide a discussion on nonlocal representations of the dispersive flux.…”
Section: ~(Xt) -;(X)~(x) Oxj (4)mentioning
confidence: 99%
“…0043-1397/98/97WR-03608 $ 09.00 neous porous media has received much attention (see Deng and Cushman [1995] and Jaekel and Vereecken [1997] for a comparison of different approaches to theoretically study solute spreading in an aquifer). When R i is larger than the empirically inferred hydraulic conductivity correlation scales hi, Ri and (c) may be described by effective dispersion coefficients Dii, which are typically much larger than the local dispersion coefficients dii.…”
Section: Paper Number 97wr03608mentioning
confidence: 99%
“…Note this last form is identical to the case presented previously by Deng and Cushman [22] and Deng et al [21] from the ensemble averaging perspective. Although the results in those works were developed using ensemble averaging methods, scaling law 3 (imposing quasi-ergodicity) makes the ensemble and volume averages interchangeable.…”
Section: Scaling Law 5: Smallness Of Variance In the Field Propertiesmentioning
confidence: 55%
“…(100). Deng and Cushman [22], considered this question, and indicated that the concentration can be removed under the conditions where the characteristic length scale of the velocity autocovariance is much smaller than the characteristic length scale for the gradient of the average concentration. Quintard and Whitaker [24] also considered this question in the context of volume averaging, and concluded that the approximation was valid when r 0 ( L. To see this latter result, one begins by generating a Taylor series for rhci as follows: r y hcij y;t 0 ¼ r x hcij x;t 0 þ ðy À xÞ Á r x r x hcij x;t 0 þ Á Á Á :…”
Section: Scaling Law 6: Smoothness Of the Average Concentration Fieldmentioning
confidence: 99%